2019
DOI: 10.1139/cjas-2018-0131
|View full text |Cite
|
Sign up to set email alerts
|

Performance, intestinal morphometry, and incubation parameters of broiler chickens submitted to in ovo feeding with different techniques and amino acids

Abstract: The objective of this research was to evaluate techniques, incubation period, and effects of amino acids in ovo feeding. First, 240 hatching eggs were selected and distributed in a 2 × 3 factorial arrangement (two techniques and 3 d). The parameters of incubation, relative weight of gastrointestinal organs, and classification of embryonic mortality were evaluated. In the second stage, 720 hatching eggs were incubated with five treatments: control, methionine (20 and 30 mg), and lysine (20 and 30 mg). These ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…No significant differences were found among treatments group for yolk sac weight (g, %). There are similar studies showing that the injection of in ovo substances has no effect on chick hatching weight (Abdulqader et al, 2018;Groff-Urayama et al, 2019;Maman et al, 2019). On the other hand, Zamani et al, (2018) reported in ovo carbohydrates injection significantly decreased the yolk sac residue compared with control group (P<0.05).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…No significant differences were found among treatments group for yolk sac weight (g, %). There are similar studies showing that the injection of in ovo substances has no effect on chick hatching weight (Abdulqader et al, 2018;Groff-Urayama et al, 2019;Maman et al, 2019). On the other hand, Zamani et al, (2018) reported in ovo carbohydrates injection significantly decreased the yolk sac residue compared with control group (P<0.05).…”
Section: Resultsmentioning
confidence: 81%
“…There are studies showing that in ovo injection of different substances has positive or negative effects on hatchability. Hatchability were adversely affected by in ovo injection propolis (Aygun 2016), amino acids (Groff-Urayama et al, 2019;Nazem et al, 2019), organic trace minerals (Oliveira et al, 2015), and vitamin D3 (Maman et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The intestinal villi are specialized structures that are very important for nutrient absorption of nutrients from the small intestine (Li et al, 2017;Groff-Urayama et al, 2019). By increasing the height of the villi, their surface area may become greater which can result in increased nutrient absorption (Marcos et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In ovo technology, which is used commercially for embryonic vaccination ( Araujo et al., 2019 ), is a viable tool for developing a wholesome chick quality and performance solution. Researchers have adopted this technology for the delivery of nutrients, ( Groff-Urayama et al., 2019 ; Hajati et al., 2014 ), antibiotics ( Hadi et al., 2014 ) and other supportive substances including plant extracts to avian embryos during incubation ( Coşkun et al., 2014a , b ; N'nanle et al., 2017 ; Sogunle et al., 2022 ; Oke et al., 2021 ), to improve hatching and growth performance of chickens as well as preventing transmission of diseases from eggs to chicks. Though the results have been promising, there exist some contradictions mainly due to the varying nutrient compositions of the substances, extraction techniques employed and the rate of injection ( N'nanle et al., 2017 ; Sogunle et al., 2022 ; Oke et al., 2021 ), which necessitate the exploration of more materials, especially plant materials to validate the in ovo injection approach.…”
Section: Introductionmentioning
confidence: 99%